A Room Temperature Route toward In Situ Crystallization of Perovskite Nanocrystals Induced by Acrylic Acid for Flexible Free‐Standing Luminescent Gels. (10th November 2022) - Wang, Dourong; Bao, Yaqi; Cui, Jingjing; Chao, Lingfeng; Gu, Lei; Hui, Wei; Shen, Yue; Zhang, Biao; Chen, Yonghua; Song, Lin
Abstract: Perovskite nanocrystals (PNCs) with unique and excellent optical properties have emerged as appealing luminescent materials in optoelectronic fields. However, high temperature processing, complicated procedures, and the use of toxic solvents are typically involved in the preparation of PNCs and their related optoelectronic devices. In this study, a one‐step method is developed for the preparation of flexible photoluminescence gel based on PNCs at ambient conditions, which is a promising alternative to the current PNCs preparation strategy in terms of experimental friendliness, ease of production, and the potential for flexible devices. Acrylic acid (AA) is used for in situ crystallization of PNCs. The interaction between H + of AA and perovskite‐solvent complex determines the nucleation and growth of PNCs. This crystallization mechanism is systematically studied by varying acid category, adjusting solvent kind, and regulating the ratio of PNCs and gels. To give a proof of practicability, flexible free‐standing PNCs‐gel composites with excellent luminescent and mechanical properties are prepared with the AA treatment. Moreover, the PNCs‐gel shape can be customized, which greatly expands the structural flexibility and functionalities of fabricated devices. Abstract : A one‐step route is developed to prepare luminescent perovskite‐gel composites at room temperature. Acrylic acid is used to induce a rapid in situ crystallization of perovskite nanocrystals (PNCs) in a polymer‐gel matrix and the corresponding mechanism is comprehensively studied. The free‐standing PNCs‐gel composites exhibit a combination of excellent flexibility and photoluminescent property.